Effect of seed and interlayer Pt thickness on spin-orbit torque efficiency in Co/Pt multilayer with perpendicular magnetic anisotropy - Lim, Gerard Joseph (2021)
As-deposited [Co/Pt] multilayers show strong perpendicular magnetic anisotropy (PMA) and spin-orbit torque (SOT). However, such structures require properly textured Pt (111) seed layers and optimized interlayer Pt thicknesses in order to maximise both PMA and SOT efficiency. In this work, the interplay of seed and interlayer Pt thickness on PMA and SOT efficiency in Ta/Pt/[Co/Pt]₃/Co/Ta multilayers was studied. Using the harmonic lock-in method, the SOT damping- and field-like efficiencies were determined, with corrections for current shunting as well as the planar Hall effect. Our measurements show that the corrected effective SOT efficiencies are at least twice as large as the uncorrected values, with damping-like efficiency of up to ∼22 Oe per 10¹⁰ A m⁻², which scales inversely with the Pt seed and interlayer thicknesses due to screening of the spin current originating from the high-resistivity bottom β-Ta layer. The choice of Pt seed and interlayer thicknesses is a compromise between PMA and SOT efficiency of the device.